Craft Development and Development through Crafts: Adaptive Strategies of Labrador Women in a Changing Fishery - Szala-Meneok, Karen; McIntosh, Kara (Anthropologica, 2022)
Like women in other coastal regions of the North Atlantic, Labrador women have a long history of adapting to the exigencies of life in a fishing, hunting and trapping society. For over 60 years crafts production has provided these women the means to contribute cash to house hold incomes, especially during times of economic hardship. In this article we explore the creation of early rural development initiatives by the International Grenfell Association and other philanthropic organizations that provided craft skills, instruction, materials and access to markets for these craft products. We explore further how these early development schemes have undergone change since their inception and how contemporary Labrador women view and organize themselves in craft-production activities within the broader context of community development issues.